Al Razi dan Rasionalisme dalam Filsafat Islam: Telaah Komprehensif atas Pemikiran dan Warisannya - Ilma Nur Asyiyah; Senja Khoerunnisa Nurpadlillah; Shadrina Fakhrana Fildzah Cahyadi; Muhamad Agus Firmansyah; Muhamad Parhan (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This article thoroughly explores the philosophical thought of Abu Bakr al-Razi, an Islamic philosopher renowned for his rationalist approach to reality, knowledge, and ethics. Al-Razi proposed the theory of five eternal principles God, universal soul, matter, space, and time which form the basis of his ontological view. In epistemology, he rejected prophetic authority and emphasized the role of reason and empirical experience in the pursuit of truth. Ethically, he linked knowledge to the well-being of the soul and practical moral values. The article also highlights Al-Razi’s critical stance toward revealed religion and prophecy, positioning him as a controversial figure in Islamic tradition. Using a qualitative-descriptive method based on literature study, this paper examines the core aspects of Al-Razi's thought and reflects on their relevance to modern philosophical discourse. The study shows that Al-Razi’s rationalism paves the way for dialogue between Islamic philosophy and contemporary views on ethics, science, and intellectual freedom.